2016
DOI: 10.1080/10942912.2016.1213742
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy for quantitative analysis and oil parameters of olive oil and virgin coconut oil: A review

Abstract: Vegetable oils are major lipid sources with high nutritional and calorific values for human diet. Specifically, virgin coconut oil (VCO) and extra virgin olive oil (EVOO) are the functional oils widely used in food and pharmaceutical products, either as vehicles or main components. The quality of edible oils is determined by its contents and parameters inherent in vegetable oils. Infrared (IR) spectroscopy is an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 46 publications
0
31
0
2
Order By: Relevance
“…Vlachos et al (2006) revealed that the absorbance intensity at 2854 cm −1 increased, whereas the band at 2925 cm −1 reduced its absorbance and increased its width during the process of heating corn oil. An increase in peak intensity at 1745 cm −1 was found during heating; the higher the intensities at 1745 cm −1 , the more carbonylic compounds present, which are formed by hydroperoxide decomposition (Rohman, 2017). Valdés et al (2015) identified the increment in absorbance intensity at 2856 and 1745 cm −1 during accelerated oxidation of blanched, roasted or fried almonds.…”
Section: Evaluation By Ft-ir Spectramentioning
confidence: 99%
“…Vlachos et al (2006) revealed that the absorbance intensity at 2854 cm −1 increased, whereas the band at 2925 cm −1 reduced its absorbance and increased its width during the process of heating corn oil. An increase in peak intensity at 1745 cm −1 was found during heating; the higher the intensities at 1745 cm −1 , the more carbonylic compounds present, which are formed by hydroperoxide decomposition (Rohman, 2017). Valdés et al (2015) identified the increment in absorbance intensity at 2856 and 1745 cm −1 during accelerated oxidation of blanched, roasted or fried almonds.…”
Section: Evaluation By Ft-ir Spectramentioning
confidence: 99%
“…Among the different types of olive oil, extra virgin olive oil (EVOO), which is the most valuable olive oil category, [3] must contain no more than 0.8% FFA content according to the relevant international organizations. Besides the FFA content, three criteria should be satisfied for olive oil to be certified as EVOO: it must be produced by mechanical extraction methods without chemicals and hot water; it must come from first cold-pressing; and it must have a perfect taste.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HAT included Oxygen Radical Absorbance Capacity (ORAC), Table 1. Fatty acid composition and non-triacylglycerol fraction of extra virgin olive oil (Huang et al, 2008;Rohman, 2017).…”
Section: Antioxidant Activities Of Olive Oils In Vitromentioning
confidence: 99%